2010
DOI: 10.1177/1948550610385473
|View full text |Cite
|
Sign up to set email alerts
|

Judgments of Power From College Yearbook Photos and Later Career Success

Abstract: Inferences from faces can predict important real-world outcomes. But little is known about the stability of these effects. Here the authors find that inferences of power from photos of the faces of the managing partners of America's top 100 law firms significantly corresponded to their success as leaders, as measured by the amounts of profits that their firms earned. More interesting, this relationship was also observed when judgments were made based on photos of the leaders taken from their undergraduate year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 30 publications
(29 reference statements)
1
27
0
Order By: Relevance
“…One of the plans for future research is to investigate other types of classes and also to investigate simultaneous separation of multiple classes. Second, information on the facial features that pre-dates the CEO appointment stemming from for instance college yearbook photos seems a promising avenue to explore the causality issue mentioned above [ 47 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the plans for future research is to investigate other types of classes and also to investigate simultaneous separation of multiple classes. Second, information on the facial features that pre-dates the CEO appointment stemming from for instance college yearbook photos seems a promising avenue to explore the causality issue mentioned above [ 47 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has shown that judgments about others' personality from facial appearance form rapidly (Rule & Ambady, 2008a) and change little over time (Willis & Todorov, 2006). Importantly, facebased trait inferences are consistent both within and across cultures , and predict important outcomes such as election results (Ballew & Todorov, 2007;Todorov et al, 2005) and career success (Rule & Ambady, 2008b;Rule & Ambady, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Targets' choice of photos on their organizations' websites may purvey a desirable appearance for their domain, but these effects should be somewhat systematic across the sample. Furthermore, previous research has shown that facial appearance predicts executives' leadership success even when the picture is taken up to 50 years before the person attains the leadership position (Rule & Ambady, 2011b). Static facial attributes based on bone structure account for a significant proportion of first impressions (Hehman, Flake, & Freeman, 2015;Vernon, Sutherland, Young, & Hartley, 2014), we therefore expect that leadership impressions should be fairly consistent across different photos of the same person.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, judgments of how powerful law firm managing partners (MPs) look also predict their firms' profits (Rule & Ambady, 2011a), even when the judgments are made from photographs of the MPs when they were college students-on average 35 years earlier (Rule & Ambady, 2011b). Mere perceptions aside, facial features typically associated with aggression and ambition can explain the relationship between some CEOs' appearance and their firms' performance, even when controlling for company performance before the current leader assumes his or her position (Re & Rule, 2016;Wong, Ormiston, & Haselhuhn, 2011).…”
mentioning
confidence: 99%